1992
DOI: 10.1103/physrevb.45.4637
|View full text |Cite
|
Sign up to set email alerts
|

Controlled mean-field theory for disordered electronic systems: Single-particle properties

Abstract: A self-consistent, conserving mean-field theory for one-particle properties of disordered electronic systems is presented. It is based on a systematic perturbation expansion in 1/Z, where Z is the coordination number of the lattice. To obtain a nontrivial limit for large Z, it is crucial to rescale the hopping integral t according to t -1/&Z. In the limit Z~00, the well-known coherent-potential approximation (CPA) is found to become exact for any lattice. Explicit proofs are presented within the locator and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 33 publications
5
85
0
Order By: Relevance
“…If in the DMFT the effect of local disorder is taken into account through the arithmetic mean of the LDOS one obtains, in the absence of interactions (U = 0), the coherent potential approximation (CPA) [30,118], which does not describe the physics of Anderson localization. To overcome this deficiency Dobrosavljević and collaborators formulated a variant of the DMFT where the geometrically averaged LDOS is computed from the solutions of the selfconsistent stochastic DMFT equations [119] which is then incorporated into the self-consistency cycle [120].…”
Section: Electronic Correlations and Disordermentioning
confidence: 99%
“…If in the DMFT the effect of local disorder is taken into account through the arithmetic mean of the LDOS one obtains, in the absence of interactions (U = 0), the coherent potential approximation (CPA) [30,118], which does not describe the physics of Anderson localization. To overcome this deficiency Dobrosavljević and collaborators formulated a variant of the DMFT where the geometrically averaged LDOS is computed from the solutions of the selfconsistent stochastic DMFT equations [119] which is then incorporated into the self-consistency cycle [120].…”
Section: Electronic Correlations and Disordermentioning
confidence: 99%
“…Studying correlated and disordered lattice fermions within statistical DMFT, we found that it is useful to compare the resulting spectral functions to those determined within the CPA. 25,54,55 Within CPA the hybridization Γ(ω) is given by…”
Section: B Interacting Systemsmentioning
confidence: 99%
“…[21][22][23] This mean-field theory is fully non-perturbative and in combination with density functional theory it is capable of describing properties of real solid-state systems. 24 An extension of DMFT, which includes disorder effects, was performed both, in analogy to the well-known coherent potential approximation (CPA), 25,26 and within a fully stochastic approach to incorporate effects of Anderson localization. 27,28 Since the latter approach is computationally very expensive if one treats correlation effects on a rigorous level and keeps sufficiently large ensembles of disorder realizations, the typical medium theory (TMT-) DMFT was developed.…”
Section: Introductionmentioning
confidence: 99%
“…(20) defines the physical interacting Green's function, see Eq. (13). Up to this point the derivations are standard.…”
Section: Configuration-dependent Self-energy Functionalmentioning
confidence: 99%
“…With a proper scaling of the model parameters this limit preserves a highly non-trivial dynamics. 12,13 This distinguished mean-field theory, for the interaction part of the problem, is the dynamical mean-field theory (DMFT). 14,15,16,17 It gives the exact (local) interaction self-energy of the prototypical Hubbard model 18,19,20 in the D = ∞ limit.…”
Section: Introductionmentioning
confidence: 99%